2018
DOI: 10.1155/2018/4384797
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Genes as Biomarkers in Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome Based on mRNA Expression Profile by Next-Generation RNA-Seq Analysis

Abstract: Up until now, the regulation mechanism at the level of gene during lipopolysaccharide- (LPS-) induced acute respiratory distress syndrome (ARDS) remains unclear. The discovery of differentially expressed genes (DEGs) between LPS-induced ARDS rats and normal rats by next-generation RNA sequencing analysis is of particular interest for the current study. These DEGs may help clinical diagnosis of ARDS and facilitate the selection of the optimal treatment strategy. Randomly, 20 rats were equally divided into 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…It is interesting that, Na, K-ATPase β1 promotes the expression of key proteins such as ZO-1, ZO-2, occludin and claudin-18 in tight junction complex and reduces the production of lung water [ 21 ]. In our study, the level of ZO-1 mRNA in lung tissue of ARDS rats induced by LPS was significantly lower than that in control group [ 22 ]. Accordingly, we speculate that increasing the level of Na, K-ATPase α1/β1 may enhance the tight junction of lung epithelium and reduce the production of lung water.…”
Section: Discussionmentioning
confidence: 93%
“…It is interesting that, Na, K-ATPase β1 promotes the expression of key proteins such as ZO-1, ZO-2, occludin and claudin-18 in tight junction complex and reduces the production of lung water [ 21 ]. In our study, the level of ZO-1 mRNA in lung tissue of ARDS rats induced by LPS was significantly lower than that in control group [ 22 ]. Accordingly, we speculate that increasing the level of Na, K-ATPase α1/β1 may enhance the tight junction of lung epithelium and reduce the production of lung water.…”
Section: Discussionmentioning
confidence: 93%
“…As previously reported ( 25 ), image analysis and base calling were performed using the Off-Line Base Caller software v1.8 (Illumina, Inc.). Sequence quality was examined using FastQC software v0.11.7 ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data from NGS not only confirm the upregulation of cytokine- and chemokine-related genes in response to lipopolysaccharides (LPS) [52], but also reveal alterations in genes related to other pathological signaling pathways. In the ventilator-induced lung injury animal model, RNA sequencing of lung tissue showed that activation of the mechanistic target of rapamycin pathway and Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling were implicated in early inflammation, while the hypoxia inducible factor-1 (HIF-1) and nuclear factor κB (NF-κB) signaling pathways were activated in the late stage, which might be related to subsequent fibrosis [53].…”
Section: Introductionmentioning
confidence: 99%